Application of Expansion and Retrenchment Strategies: A Case Study of Zain Group - Pankhurri Semwal; Ahmad Ariq Rabbani (IJEBD (International Journal of Entrepreneurship and Business Development), 2018)
This paper discussed the supply chain management solutions at PT Coca Cola Bottling Indonesia with an evaluation of supply chain management of Coca Cola, where supply chain management is a concept or mechanism to increase the total productivity of companies in the supply chain through optimization of the time, location and quantity of flow materials from raw materials into semi-finished products and finished products. Supply Chain Management is not only about the relationship with the supplier but also the link between the company and consumers. By knowing the value of the performance of supply chain the company can improve the effectiveness and productivity of the organization to achieve organizational goals is to win the competition, and increase corporate profits. In such measurements should be made an integrated framework and must comply with the conditions of the studied companies.